النظام القانوني للجمركي في التشريع الجزائري - عبد الناصر عثماني; سناء طواهرية (My University, 2025)
Summary of the Memorandum This memorandum aims to study the legal system of customs officers in Algerian legislation. It highlights the legal and regulatory framework that defines their duties, rights, obligations, and the responsibilities associated with their roles. Customs officers are responsible for protecting the national economy and combating fraud and smuggling across borders, placing them in a sensitive position that requires careful organization to balance authority and responsibility. The memorandum addresses the legal status of customs officers, including conditions for employment, training, and promotion. It also reviews the powers granted to them during the performance of their duties, such as inspection, seizure, and follow-up. Additionally, the memorandum discusses the forms of responsibility that customs officers may bear, whether disciplinary, criminal, or civil, due to exceeding legal limits or abusing authority. The memorandum concludes that there is a need to update the legal texts governing the customs sector, enhance the training of officers, and provide legal protection for them while performing their duties, without compromising the principles of accountability and legal liability. ........................... Résumé Cette note vise à étudier le cadre juridique de l'agent des douanes dans la législation algérienne, en mettant en évidence le cadre légal et réglementaire qui définit ses missions, ses droits, ses devoirs et les responsabilités qui en découlent lors de l'exercice de ses fonctions. L'agent des douanes est chargé de protéger l'économie nationale et de lutter contre la fraude et la contrebande aux frontières, ce qui le place dans une position sensible nécessitant une organisation précise équilibrant pouvoir et responsabilité. La note aborde la situation juridique de l'agent des douanes, en ce qui concerne les conditions d'emploi, de formation et de promotion, ainsi que les pouvoirs dont il dispose lors de l'exercice de ses fonctions, tels que la fouille, la saisie et le suivi. Elle traite également des formes de responsabilité que l'agent des douanes peut encourir, qu'elles soient disciplinaires, pénales ou civiles, en raison d'un dépassement des limites légales ou d'un abus de pouvoir. La note conclut à plusieurs résultats, parmi lesquels la nécessité de mettre à jour les textes juridiques régissant le corps des douanes, de renforcer la formation des agents, tout en leur offrant une protection juridique lors de l'exercice de leurs fonctions, sans compromettre le principe de responsabilité et de reddition de comptes.
Keywords: Keywords: customs officer; rights; obligations; training; responsibility.; الكلمات المفتاحية: العون الجمركي، حقوق، واجبات، التكوين، المسؤولية.; Mots-clés: Agent des douanes - Législation algérienne – Responsabilité - Protection économique – Formation .